PARAMEDIAN FOREHEAD FLAP FOR RECONSTRUCTION OF THE NOSE - Al Hafiz; Effy Huriyati; Bestari J. Budiman; Jacky Munilson (Faculty of Medicine, Universitas Andalas, 2015)
AbstrakPenutupan defek yang ditimbulkan akibat operasi di daerah kepala dan leher umumnya dapat dilakukan dengan penjahitan langsung. Untuk defek yang lebih luas, atau apabila metode penjahitan langsung tidak memungkinkan untuk dilakukan, maka dapat digunakan flap kulit. Laporan kasus ini bertujuan untuk mendemonstrasikan ke ahli THT-KL, bagaimana forehead flap dapat memperbaiki estetika dan fungsi hidung pada kasus deformitas hidung. Satu kasus deformitas pada hidung, seorang laki-laki berusia 69 tahun dengan riwayat basalioma di daerah hidung. Pada pasien dilakukan rekonstruksi hidung dengan menggunakan forehead flap. Rekonstruksi hidung menggunakan forehead flap dapat mengurangi defek pada deformitas hidung. Diperlukan analisis wajah terutama daerah hidung untuk menentukan jenis dan posisi dari flap kulit yang tepat.AbstractA Defect following head and neck surgery can often be closed using the technique of direct suture. For larger defects or in situations where direct suture is neither applicable, surgical defect in the head and neck especially at the nose, can be filled by local skin flaps. The case was reported in order to demonstrate to Otorhinolaryngology Head and Neck surgeons on how the forehead flap could restore the aesthetic and function of the nose in nasal deformity case. One case of the nasal deformity was reported in a 69 years old man with history of basal cell carcinoma on the nose. This patient was managed using the forehead flap for nasal reconstruction purpose. The employment of this technique could reduce the defects of nasal deformity. Facial analysis particularly nasal area is necessary to determine the exact kind and position of skin flap.